Impact of nearshore vegetation on coastal dune erosion: assessment through laboratory experiments - Turker, Umut; Yagci, Oral; Kabdasli, M. Sedat (Springer, 2019)
The primary objective of this study was to delineate the impact of vegetation on dune erosion under the influence of storm waves. This was achieved through laboratory flume experiments. Specifically, physical model experiments were used to identify the features responsible for coastal dune erosion generated by storm waves under the protection and non-protection of vegetation cover. Observations were then formulated based on the effective variables such as wave height and period, vegetation and sediment characteristics through Buckingham pi theorem to obtain dimensionless parameters like fall speed, vegetation length, depth and wave steepness parameters. Among the dimensionless parameters, the vegetated length parameter was effective in defining, measuring and comparing the coastal dune erosion. Based on vegetated length parameter, the change in erosion volume per unit width was calculated as 9.7-74% for regular wave conditions and 2.9-70.1% for irregular wave conditions. Furthermore, as the vegetated length parameter reduced wave damping ratio was not significantly affected, whereas the increase in the vegetated length parameter increases the wave damping ratio up to 0.5. As a result, the wave attenuation was recorded between 45 and 50%. An approach to correlate the wave energy coming out of the vegetation field with the energy necessary to erode the coastal dune profile depicted a linear correlation. As a result, empirically based equations have been developed to be used in soft coastal defense approaches which predict the volume of dune erosion and the wave attenuation under the protection of emergent vegetation. In addition, the energy required for the evolution of dune erosion is formulated in terms of attenuated wave energy.
Keywords: Coastal dune; Erosion; Vegetation; Wave attenuation; Wave energy